Spinach Growth under Various Combinations of Sugarcane Biochar and Water Hyacinth Liquid Organic Fertilizer - Nani; Agusta, Herdhata; Melik Thiara Dikari; M Juhri Al Karomah (Jurnal Pertanian, 2025)
Biochar and liquid organic fertilizer (POC) can be combined to enhance plant growth. This study aimed to evaluate the effects of applying sugarcane bagasse biochar and water hyacinth liquid organic fertilizer (POC) on soil properties and the growth of vegetable crops, particularly pakcoy (Brassica rapa L.) and spinach (Amaranthus sp.). Initial soil analysis showed a pH of 6.97 with high levels of potassium (K) and nitrate (NO₃⁻). The biochar used had an alkaline pH of 8.83, a fixed carbon content of 63.2%, and was classified as grade A according to the Indonesian Ministry of Agriculture standards. Meanwhile, the water hyacinth POC had an acidic pH of 4.02 with a high nitrate content (6,700 ppm). Observations indicated that biochar application up to 20 tons/ha increased the number of leaves, leaf area, and dry weight of pakcoy, while higher doses tended to reduce growth. Application of water hyacinth POC significantly increased the fresh weight of spinach compared to the control. The combination of biochar and POC demonstrated great potential in improving soil fertility and enhancing vegetable crop yields. This study recommends the use of biochar and POC at appropriate dosages to support sustainable agriculture on Andosol soils. Keywords: Biochar, Liquid Organic Fertilizer, Soil Fertility, Plant Growth, Sustainable Agriculture